HUMAN-WILDLIFE CONFLICTS AND MITIGATION MEASURES IN PENDJARI BIOSPHERE RESERVE, NORTHERN BENIN - EFIO, Sylvain; SOGBOHOSSOU, ETOTEPE A.; MAGNON, Z. YVES; HOUINATO, MARCEL ROMUALD BENJAMIN; HABIYAREMYE, M; SINSIN, Brice; TOSSOU, COCOU RIGOBERT (My University, 2018)
Human-wildlife conflicts are any interactions between human and wildlife with a negative impact for both parties. Understanding these conflicts is necessary to guaranty a better coexistence between human and wildlife and an improvement of wildlife conservation. The current research aims at assessing humanwildlife conflicts and analyzing the management measures developed by local communities around Pendjari Biosphere Reserve in Benin. Data were collected in January and February 2017 through a questionnaire survey of 245 respondents from different socio-professional background. Three main types of conflicts were observed around the Reserve: crop raiding, livestock predation and destruction of fishing materials. The most destroyed crops were maize (15 %), cotton (15 %) and millet (14 %), and sorghum (29 %) and baboon was the most important crop raiding species (61 % of depredation cases). Regarding livestock, pig (25 %) and sheep/goat (23.1 %) were the most attacked animals while hyena was the most important predator reported (40.6 % of attacks). Fishing nets and hoop nets were destroyed by crocodile (72.2 %) and hippopotamus (27.8 %). To reduce these damages, farmers used several measures such as guarding (82%), scarecrows (64.5 %), and fires on the outskirts of the fields (67.3 %). Herders mostly used livestock’ guarding (12.7 %) and fires or torchlight lit in the enclosures during the night (8.6 %). These measures were not efficient to prevent or avoid the damages but they did reduce them. They must be reinforced to reduce the impact of the damages on the agricultural production, the main source of income of local communities.
Keywords: Human-wildlife coexistence; damage; predation; conflicts mitigation; West Africa